Relationship Between Patient SWAP-200 Personality Characteristics and Therapist-Rated Therapeutic Alliance Early in Treatment. Issue 6 (June 2016) - Smith, Scott W.; Levy, Saryn R.; Hilsenroth, Mark J.; Fiori, Katherine; Bornstein, Robert F.
Abstract : Abstract: In the present study, we assess the extent to which patient personality features and prototypes are associated with early treatment therapist-rated alliance. The study sample consisted of 94 patients receiving psychodynamic psychotherapy at an outpatient clinic. Clinicians completed the Working Alliance Inventory ( J Couns Psychol 36:223–233; Psychother Res 9:405–423) to assess their views of early alliance and the Shedler-Westen Assessment Procedure 200 (SWAP-200; Assessment 5:333–353, Am J Psychiatry 161:1350–1365, 1743–1754; Am J Psychiatry 156:258–272, 273–285) to assess patient personality. The SWAP-200 Narcissistic Clinical Prototype, Dysphoric Q-Factor, and Dysphoric/High-Functioning Neurotic Q-Subfactor significantly correlated with early therapist-rated alliance. Correlations that trended toward significance were also found. Also identified were specific SWAP-200 items that were found to relate to high early therapist-rated alliance scores. These results demonstrate some relationship, albeit small, between patient personality characteristics and therapists' views of the alliance that may serve to further a conceptual understanding of the alliance, specific personality syndromes, and the associated impact on the therapeutic interaction.